In-vivo assessment of myocardial calcium uptake using manganese-enhanced cardiovascular magnetic resonance in aortic stenosis - Abhishek Dattani; Saadia Aslam; Gaurav S. Gulsin; Aseel Alfuhied; Trisha Singh; Shruti S. Joshi; Lucy E. Kershaw; David E. Newby; Gerry P. McCann; Anvesha Singh (Journal of Cardiovascular Magnetic Resonance)
Background: Dysregulated myocardial calcium handling has been demonstrated in ischemic, non-ischemic and diabetic cardiomyopathy. Manganese-enhanced MRI (MEMRI) provides a unique method to quantify in-vivo myocardial calcium uptake but no studies have so far utilized MEMRI in patients with aortic stenosis (AS). We sought to: 1) determine whether myocardial calcium uptake is perturbed in people with severe AS, and 2) assess change in calcium uptake following aortic valve replacement (AVR). Methods: In this prospective, pilot, case-control study, adults with severe AS underwent MEMRI before and after AVR. A group of healthy controls were also recruited. The primary outcome was the rate of manganese uptake (Ki) as assessed by Patlak modeling to act as a surrogate of myocardial calcium uptake. Comparison of Ki between groups was adjusted for age, body mass index (BMI) and systolic blood pressure. Results: Twenty-eight controls and ten subjects with severe AS (age 72 [61-75] years, 8 male, 7 symptomatic, valve area 0.81 [0.74-1.0] cm2) were recruited, with seven returning for repeat scans post-AVR. AS patients had higher BMI and blood pressure, and a greater incidence of hyperlipidemia compared to controls. Baseline left ventricular (LV) volumes were similar between the groups, but the AS patients had higher indexed left ventricular mass. Global longitudinal strain and peak early diastolic strain rate were lower in the AS group. There was no significant difference in Ki between patients with severe AS and controls (7.09 [6.33-8.99] vs. 8.15 [7.54-8.78] mL/100g of tissue/min, P=0.815). Following AVR, there was regression in indexed LV mass (68 [51-79] to 49 [47-65] g/m2, P=0.018) and mass-volume ratio (0.94 [0.80-1.13] to 0.74 [0.71-0.82] g/mL, P=0.028) but no change in Ki was seen (7.35 [6.81-8.96] to 7.11 [6.16-8.01] mL/100 g of tissue/min, P=0.499). Conclusions: Despite clear features of adverse LV remodeling and systolic dysfunction, patients with severe AS demonstrated no alteration in calcium uptake at baseline compared to controls. Moreover, AVR led to reverse LV remodeling but no notable change in calcium uptake was seen. This may suggest that altered myocardial calcium handling does not play a significant pathophysiological role in AS.